Life after loss: The causal effect of parental death on daughters' fertility - Felix Glaser; Rene Wiesinger (Johannes Kepler University of Linz, Department of Economics, 2024)
We use high-quality administrative data from Austria to credibly identify the causal effect of parental death on daughters' fertility. To account for the endogeneity of parental death, we exploit the timing of deaths in a difference-in-differences research design. Parental death has no statistically significant effect on daughters' fertility, even in situations where the loss of informal childcare should be particularly pronounced. The absence of a fertility effect is strengthened by an extensive series of robustness checks and results on complementary outcomes, including labor market participation, place of residence, and mental health. Our findings suggest that women do not make significant adjustments to important life decisions after the loss of a parent.
Keywords: J13; J10; J20; I10; 330; Parental death; fertility; difference-in-differences